Agrotóxicos e abelhas: cienciometria e análise de efeito residual de imidaclopride e beta-ciflutrina em canola Brassica napus L. - Abati, Raiza (2021)
Bees are fundamental insects in agroecosystems, mainly due to pollination. However, its decline has been observed and the contamination by pesticides are suspected to be responsible. In this sense, the objective of this work was to evaluate the relationship between pesticides and bees. For this, a scientometric review, a review on sublethal effects caused by neonicotinoids in Apis mellifera and a bioassay on the toxicity of the residual effect of insecticides to workers of A. mellifera. The scientometric review was performed with data obtained from the Web of Science database (1,231) and were analyzed using Microsoft Office Excel and CiteSpace. The results point to a significant increase in pesticide and bee reseach in the last 15 years. The USA and France have the largest number of publications and a moderade relationship between this trait and Gross Domestic Product (GDP) was observed. When verified the sublethal effects caused by neonicotinoids on A. mellifera it was observed that they compromise the physiology of bees, interfering in the transcription of genes and metabolism, intestinal microbiota and in the semen quality. In addition, they compromise colony performance and negatively influence learning, memory, motor activity and communication dance, factors that compromise the balanced development of colonies, contributing in the medium and long term to the disappearance of bees. Finally, in an experiment started in a semifield and conducted in the laboratory, workers of A. mellifera were exposed to canola plant material containing residual imidacloprid, betacyfluthrin and the mixture of these in 14, 09, 06, 03 and 0 days after application. Bees' longevity was assessed for 96 hours. A reduction in the survival of the bees can be observed when compared to the control, so that the shorter the interval between the time of application of the product in the field and the contact of the bees, the lower the survival of the bees. The product containing only betacyfluthrin caused higher mortality and maintained greater residual over the days, when compared to other treatments. Alternative to chemical methods are needed to control pest insects in canola culture to reduce damage to pollinators. In general, studies have shown negative effects of pesticides on bees, however, most publications are related to bees of the genus Apis and, therefore it is necessary to explore the action of these products on stingless bees, solitary bees and genus Bombus, as well as studies evaluating the sublethal effects of these products, considering that the number of molecules used in the management of agricultural crops is vast.